French Politics and Alfred Loisy's Modernism - Hill, Harvey (Church history, 1998)
The first decade of the twentieth century was a time of great theological ferment in the Catholic church in France. In order to reconcile Catholic teaching with the latest findings of historical criticism, Alfred Loisy (1857–1940) and other “modernists” proposed sweeping reforms in the Church. From the perspective of Rome, however, these reforms seemed to threaten the very heart of the faith. In Roman eyes, Loisy and his theological allies had adopted the scientific methods of the anticlerical university. Like their secular colleagues but less openly, they then used these methods to subvert the Catholic tradition and the institutional structure of the church. The Vatican defended its embattled faith with a series of measures designed to crush this movement.